Prenatal Counseling and Diagnosis of COX20 Gene-Related Mitochondrial Complex IV Deficiency: A Case Report and Literature Review - Su J; Zeng L; Chen H; Tong J; Chen Y; Huang L; Deng L; Huang Y (International Journal of Women's Health)
Junyou Su,1,* Lingdong Zeng,2,* Hongfei Chen,1 Junru Tong,1 Yan Chen,1 Lingling Huang,1 Li Deng,1 Yan Huang1 1Department of Obstetrics, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, 530007, People’s Republic of China; 2Department of Pediatrics, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, 530007, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Deng; Yan Huang, Email dengli@gxmu.edu.cn; huangyanHY2020@163.comBackground: COX20-related mitochondrial complex IV deficiency is a rare autosomal recessive metabolic disorder that arises from biallelic loss-of-function mutations. Given the lack of specific treatments, affected children are at a heightened risk of disability. Consequently, prenatal counseling and prenatal diagnosis should be conducted to reduce the birth rate of children with such mitochondrial diseases. We report a case of COX20 gene associated mitochondrial complex IV deficiency in a child, and describe the prenatal counseling and prenatal diagnosis of the mother in subsequent pregnancies to provide reference for prenatal counseling and prenatal diagnosis of this disease.Case Presentation: In this study, we presented a case of a pediatric patient who displayed symptoms such as gait instability, ataxia, cognitive impairment, dysarthria, muscle weakness, and absent reflexes. Through the application of whole-exome sequencing (WES), compound heterozygous COX20 mutations (c.41A>G and c.259C>T) were detected, leading to the confirmation of a diagnosis of mitochondrial complex IV deficiency. A thorough review of the existing literature revealed seven additional cases carrying the same mutations. Moreover, this report delineated the process of prenatal counseling and diagnostic testing that was undertaken for the subsequent pregnancy of the patient’s mother.Conclusion: The presence of ataxia, cognitive impairment, and peripheral neuropathy in children should prompt consideration of COX20-related mitochondrial disease. Utilizing WES is beneficial for identifying COX20 mutations, and offering prenatal counseling and diagnostic testing to mothers of affected children can reduce the birth rate of children with such mitochondrial diseases.Keywords: COX20, complex IV deficiency, prenatal counseling, prenatal diagnosis